1883 N.Y. Pen. Code 142, tit. 13, § 468 - (:unkn) unknown (General Publisher, 1883)
A person, who willfully discharges any species of firearms, air-gun, or other weapon, or throws any deadly missile in any public place, or in any place where there is any person to be endangered thereby, although no injury to any person shall ensue, is guilty of a misdemeanor.
--
Keywords: DISCHARGE